Papua New Guinea : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2011)
Papua New Guinea (PNG) was only mildly impacted on the financial front during the global crisis. Although the financial sector in PNG has been a source of strength in 2000, vulnerabilities exist and need to be carefully managed. There are important steps needed to strengthen the regulation and supervision of the banking and insurance sectors. The development of local government securities markets is important for system stability. Five years after the enactment of the Proceeds of Crime Act (POCA), there is still no legislation on terrorist financing.